2008
DOI: 10.1159/000121383
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy (HBO) for the Treatment of an Epidural Abscess in the Posterior Fossa in an 8-Month-Old Infant

Abstract: Epidural abscesses in children are extremely rare, especially in the posterior fossa. In some cases antibiotic therapy and surgical drainage are insufficient for complete healing. We present the case of an 8-month-old boy who developed an epidural abscess in the posterior fossa after repeated surgical procedures for retrocerebellar arachnoid cysts and hydrocephalus. We decided to use adjuvant hyperbaric oxygen therapy (HBO) to avoid removal of the bone and the existing ventriculoperitoneal shunt. In this way o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Since systemic infection by multiple oral bacteria often occurs after dental events ( 12 ), systemic infection in the present case may have been caused by the tooth extraction. To our knowledge, besides cases due to the spread of otitis externa caused by Pseudomonas aeruginosa , there have been 14 reported cases of central skull-base osteomyelitis in which the causative organism was successfully determined ( 2 - 9 , 13 - 18 ). Among those 14 cases, 8 were due to oral bacteria, including 4 cases caused by Fusobacterium species and 1 case caused by Fusobacterium nucleatum .…”
Section: Discussionmentioning
confidence: 99%
“…Since systemic infection by multiple oral bacteria often occurs after dental events ( 12 ), systemic infection in the present case may have been caused by the tooth extraction. To our knowledge, besides cases due to the spread of otitis externa caused by Pseudomonas aeruginosa , there have been 14 reported cases of central skull-base osteomyelitis in which the causative organism was successfully determined ( 2 - 9 , 13 - 18 ). Among those 14 cases, 8 were due to oral bacteria, including 4 cases caused by Fusobacterium species and 1 case caused by Fusobacterium nucleatum .…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant HBOT therapy was successfully applied for retrocerebellar arachnoid cyst and hydrocephalus to an 8-month case of epidural abscess in the posterior fossa after repeated surgical operations. There was no need for a ventriculoperitoneal shunt and bone removal process (1). Minimal side effects were recorded for the HBOT treatment and it involved momentary pressure equalization problems.…”
mentioning
confidence: 99%
“…It is reported that HBOT can be used as a safe treatment method for iatrogenic cranial and spinal infections after brain surgery (6,7,9). Oxygen has a direct antimicrobial effect, particularly on anaerobes, and the oxygen in hypoxic tissues can lead to restoration of white blood cells and antimicrobial functions (1). A 68-year-old male patient diagnosed with hypopharyngeal carcinoma who underwent chemoradiotherapy was later treated with HBOT due to the high risk of surgical treatment for the cervical spine osteomyelitis and epidural abscess and a large defect in the posterior hypopharyngeal region that developed after the initial treatment.…”
mentioning
confidence: 99%